Analysis of the relationship between treatment patterns based on patient characteristics in cases of hypertension complications at PKU Muhammadiyah Gamping Hospital - Ariansyah, Diffa Zahra; Wulandari, Ari Susiana; Estiningsih, Daru; Nurinda, Eva (Alma Ata University Press, 2024)
Background : Hypertensive disease is often referred to as